Teachers’ Perceptions on Using Smartphones in English as a Foreign Language Context - Ali Abbas Alzubi (Research in Social Sciences and Technology, 2019)
This study explored the perceptions of English as a foreign language (EFL) teachers at a foundation year in a university in Saudi Arabia. 41 male (27) and female (14) teachers completed a survey using Google Forms. The results indicated that the majority of teachers (83%) supported the integration of smartphones in EFL context, as 71% believe that smartphones would enhance students’ EFL learning. 72% reported that they used smartphones for university-related work. Sending and receiving emails, accessing the internet, and using educational applications were the most reported beneficial features whereas scanning/creating QR codes, using calculator, playing games, and playing a podcast were the least reported. 79 % believed that smartphones would have instructional benefits for the learners such as access to technology, motivation, creativity English language learning opportunities, and variation in instruction whereas 58 % did not see any barriers in the use of smartphones in EFL context. That smartphones may distract students’ attention was the only reported barrier. Recommendations and impactions for further research and applications were suggested.